Optical Ray Tracing Simulation by Using Monte Carlo Method for Reflectance-based Photoplethysmography Sensor in Human Skin and Fingertip Model - Misran, Muhamad Affiq Bin; Bilgaiyan, Anubha; Hattori, Reiji (Computational And Experimental Research In Materials And Renewable Energy, 2022)
The pulse oximetry device has been used for decades to monitor human pulse rate and oxygen saturation. There are two types of pulse oximetry which are transmission and reflection based. However, most devices are unsuitable for daily health monitoring due to the bulkiness and inconvenience of long-term monitoring while continuously doing everyday activities. Therefore, developing a wearable device such as a patch would benefit the users. Several factors can be considered for such a system. One of them is the distance between the source and detector since both are the major components of this system. However, there is still a lack of information in this regard. This study used the ray-tracing Monte Carlo method to simulate transmittance and reflectance-based oximetry principles with a 663 nm wavelength as the light source. The results show the ray tracing behavior from the light source to the photodetector in the biological tissue under two different structures mentioned previously. The separation between the light source and the detector should be less than 3 mm for the reflection type. A significant difference was observed for a distance greater than 3 mm compared with the transmission-based, which has a higher photocurrent even at a 7 mm distance. However, this transmission-based device is limited to the placement of the device on the body part. It is due to the thickness, which varies depending on the body parts themselves. Therefore, wearable pulse oximetry devices with the reflectance-based principle are better due to higher signal acquisition than the transmittance-based, especially for the daily health monitoring system. Furthermore, it also can be used throughout any body part. This reflection-based device can fully utilize microfabrication to integrate the light source and photodetector.Keywords: PPG sensor, Monte Carlo, tissue optics, pulse oximetry, photoplethysmography.